HUBUNGAN TIPE MELASMA DENGAN JENIS KULIT PADA WANITA USIA REPRODUKTIF - Ariando; Tarigan, Juliyanti; Tarigan, Mawar (Jurnal Kedokteran Methodist, 2022)
Background : Melasma is one of the most common skin problems. The onset of melasma causes disturbances in the facial skin as well as causes a decrease in self-confidence in sufferers. Melasma can affect all races, especially people living in the tropics. Indonesian people who have a lot of dark skin have melanin-producing cells which tend to be larger to produce melanosomes. This incident occurs in people who are often exposed to sunlight, making sun exposure the main trigger for melasma. Objective: To determine the relationship between melasma type and skin type in women of reproductive age. Methods: This study uses a literature study or literature review method. The design of this research is observational analytic, the data sources are obtained from journals, books, documentation, internet and libraries. Results: Based on a literature review of the relationship between melasma and skin type in women of reproductive age, it was found that skin types III-V are genetic predisposing factors for the occurrence of melisma. There are risk factors, namely the length of exposure to sunlight, the use of cosmetics, the hormone estrogen, and the hormone melanin synthesis associated with melasma. There are 3 journals related to the prevalence of melasma in women of reproductive age. In 2 journals, there was a relationship between the type of melasma in women of reproductive age and the most in the mixed type. Conclusion: Based on this study, it can be concluded that there is a relationship between skin type, risk factors, prevalence of melasma, and type of melasma with women of reproductive age.